Heterotrophic Nitrogen Fixation at the Hyper-Eutrophic Qishon River and Estuary System - Geisler, Eyal; Bogler, Anne; Bar-Zeev, Edo; Rahav, Eyal (Frontiers in Microbiology, 2020)
Planktonic heterotrophic diazotrophs (N2-fixers) are widely distributed in marine and freshwater systems, yet limited information is available on their activity, especially in environments with adverse conditions for diazotrophy (e.g., N-rich and oxygenated). Here, we followed the localization and activity of heterotrophic diazotrophs in the hyper-eutrophic N-rich Qishon River—an environment previously considered to be unfavorable for diazotrophy. Our results indicate high heterotrophic N2 fixation rates (up to 6.9 nmol N L–1 d–1), which were approximately three fold higher at an upstream location (freshwater) compared to an estuary (brackish) site. Further, active heterotrophic diazotrophs were capture associated with free-floating aggregates by a newly developed immunolocalization approach. These findings provide new insights on the activity of heterotrophic diazotrophs on aggregates in environments previously considered with adverse conditions for diazotrophy. Moreover, these new insights may be applicable to other aquatic regimes worldwide with similar N-rich/oxygenated conditions that should potentially inhibit N2 fixation.